Performance comparison of TOPAS chirped fiber Bragg grating sensor with Tanh and Gaussian apodization - Dedi Irawan; Khaikal Ramadhan; Saktioto Saktioto; Azwir Marwin (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
In this work we carried out a numerical simulation with software Optigrating for Apodization chirped fiber Bragg grating (CFBG) with TOPAS material to improve sensitivity sensor, it was found that CFBG with a grating length of 50 mm has advantages in terms of ripple factor, side lobe left (SLL), and side lobe right (SLR) with values of -0,998 and -10,5264 dB, respectively. While the 10 mm CFBG has a narrower full-width half maximum (FWHM) with a value of 0.4528 nm. Tanh and Gaussian apodization were arranged in the CFBG design, it was found that the Tanh linear-CFBG had a narrow FWHM but for the ripple factor and the main lobe and side lobes were not good enough compared to the Tanh Cubicroot-CFBG, and the same pattern was also obtained in the Gaussian apodization. The narrow FWHM indicates the accuracy in detecting temperature, as well as the suppression of SLL and SLR. for the effect of apodization on CFBG it was found that The Tanh Linear-CFBG design with TOPAS material has the highest sensitivity which is -51.76 pm/oC compared to other designs.